2005
DOI: 10.1088/0031-9155/50/21/010
|View full text |Cite
|
Sign up to set email alerts
|

A pencil beam algorithm for intensity modulated proton therapy derived from Monte Carlo simulations

Abstract: A pencil beam algorithm as a component of an optimization algorithm for intensity modulated proton therapy (IMPT) is presented. The pencil beam algorithm is tuned to the special accuracy requirements of IMPT, where in heterogeneous geometries both the position and distortion of the Bragg peak and the lateral scatter pose problems which are amplified by the spot weight optimization. Heterogeneity corrections are implemented by a multiple raytracing approach using fluence-weighted sub-spots. In order to derive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
233
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(237 citation statements)
references
References 29 publications
4
233
0
Order By: Relevance
“…[8][9][10] Previous dose algorithms for SSPT normally used a single Gaussian (SG) function to describe the shape of an in-air lateral profile of an individual pencil beam. 4,11 However, our recent works have demonstrated that a SG function could not describe in-air lateral profiles well for an individual pencil beam from our scanning nozzle. [12][13][14][15] The TPS vendor, therefore, implemented a double Gaussian (DG) fluence model to account for the spot fluence due to contributions of large angle scattering from the devices within the scanning nozzle.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…[8][9][10] Previous dose algorithms for SSPT normally used a single Gaussian (SG) function to describe the shape of an in-air lateral profile of an individual pencil beam. 4,11 However, our recent works have demonstrated that a SG function could not describe in-air lateral profiles well for an individual pencil beam from our scanning nozzle. [12][13][14][15] The TPS vendor, therefore, implemented a double Gaussian (DG) fluence model to account for the spot fluence due to contributions of large angle scattering from the devices within the scanning nozzle.…”
Section: Introductionmentioning
confidence: 81%
“…The low-dose envelope due to nuclear interactions changes with depth for a given proton energy, building up and reaching the maximum at an intermediate depth, and then receding. 11,14,15 The TPS must accurately model this variation. The observed larger differences at some intermediate depths for high proton energies (e.g., 23.2 cm for 221.8 MeV, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 and 9͒, and generate beam data for commissioning treatment planning software. 10 The last application requires a general purpose model that is accurate inside and outside the primary field to interpolate between measured data and/or estimated corrections due to nuclear interactions in the superposition of pencil beams. 11 Second, we use the model to determine the source of the radiation and the contributions from neutrons, which have high linear energy transfer ͑LET͒, and photons and scattered primary protons, which have low LET.…”
mentioning
confidence: 99%
“…The pencil beam kernel represents the dose distribution in water created by an elementary pencil beam of unit fluence with kinetic energy corresponding to the beam's full range, and can be calculated using various combinations of physics models and/or measured data. [13][14][15] Because pencil beam algorithms are based on dose kernels computed in water, an important consideration is how to properly account for tissue heterogeneities that occur within the patient. Most pencil beam algorithms use path length scaling with or without proton transport theory to model the effects of material heterogeneities on the treatment beam.…”
Section: Introductionmentioning
confidence: 99%